Determination of induction motor parameters using LabVIEW - Zhou, Wenkang (2016)
Induction motor is now having abundant usage as industrial drives in a wide variety of industrial area including oil gas, logistics and manufacturing since the rapid industrial development after industrial revolution. Nowadays, to increase the performance and reliability of induction motor, various kinds of testing on induction motors can be implemented on the graphical programming based tool LabVIEW with DAQ system. In this project report, an induction motor is tested by ten cycles using oscilloscope. LabVIEW interface programs are designed to conduct the no load test and locked rotor test on induction motor to find the equivalent circuit parameters. Instead of using ammeter, voltmeter and power analyser, data acquisition mechanism with voltage and current sensor is adopted. Inductor motor modelling developed in LabVIEW is based on the mathematical expressions. The simulation and online measurement results are used to be compared and validated with the result of oscilloscope. To monitor motor’s power quality and motor performance, a LabVIEW interface program is designed to measure power factor, output power, induced torque and motor efficiency online at any load conditions. The report also presents the connection of voltage and current sensor, the experiment setup and detailed algorithms to design the interface program.